Remarks on Orthographic Characteristics of The Aton Transcription of Dušan’s Code - Antic, Aleksandra M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The paper describes the spelling of the consonants j, lj, nj, ć and đ and the groups consisting of the aforementioned consonants and vowels in The Aton Transcription of Dušan’s Code, written in the first half of the 15th century. The paper discusses the way of recording voices for which there were no special graphemes in either Old Slavonic or Older Serbian Cyrillic. The Athos transcript of Dušan’s Code examined the writing of the sonatas j, lj, nj and the consonants ć and đ, as well as the voice groups of the groups [ja], [je], [jo], [ju], [ji], [lja], [ ljе], [ljо], [lju], [lji], [njа], [njе], [njо], [nju], [nji], [ćа], [ćе], [ćо], [ću] , [ći], [đa], [đe], [đo], [đu] and [đi], and the obtained results were then compared with the situation in the Baranja transcript. A statistical model was used to represent the distribution of competitive graphics in the studied manuscripts.